Algebra for dummies - Sterling, Mary Jane (Wiley, 2006)
Algebra gives you the power to be able to help someone else with an algebra task or to explain to a friend about these logical mathematical processes. Algebra is a system of symbols and rules that is universally understood, no matter what the spoken language.Algebra provides a clear, methodical process that can be followed from beginning to end. It's an organizational tool that is most useful when followed with the approciate rules.